Factors Influencing The Incident Of Perineal Rupture In Makassar City Hospital - Safitria Aini Talib; Dwi Ghita; Andi Sulfikar (Ammar Dharma Foundation, 2024)
Background: Perineal rupture is a tear in the perineum or injury to the birth canal that occurs during the birth of a baby, whether using tools or not. Perineal rupture occurs in almost all first deliveries and is not uncommon in subsequent deliveries. Factors causing perineal rupture consist of maternal factors such as: parity, partus precipitatus, prolonged labor and maternal age. Fetal factors include: large baby, abnormal head position, breech birth and shoulder dystocia.Objective: The aim of this research was to determine what factors influence the occurrence of perineal rupture in the Makassar City Regional Hospital.Research Method: The type of research carried out is quantitative descriptive research with a retrospective approach. The sampling technique in this research is Non Probability Sampling using the Purposive Sampling method.Results: After carrying out the Chi-square statistical test, each significance value was obtained for maternal parity ρ = 0.000 < α 0.05, significance value for maternal age ρ = 0.002 < α 0.05, and significance value for birth weight ρ = 0.000 < α 0.05 So Ha is accepted and H0 is rejected, which means there is an influence between parity, maternal age and birth weight on the incidence of perineal rupture at Makassar City Regional Hospital.Suggestion: It is hoped that future researchers will be able to conduct more in-depth research on childbirth.